2013
DOI: 10.1111/apa.12193
|View full text |Cite
|
Sign up to set email alerts
|

How to administrate erythropoietin, intravenous or subcutaneous?

Abstract: In preterm infants, continuous intravenous administration of erythropoietin was not inferior to SC dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Recombinant erythropoietin (rhEPO) is an example of a drug commonly administered subcutaneously; however, subcutaneous administration of rhEPO requires injection three times a week, a likely cause of discomfort for the neonate [79,80].…”
Section: Subcutaneousmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant erythropoietin (rhEPO) is an example of a drug commonly administered subcutaneously; however, subcutaneous administration of rhEPO requires injection three times a week, a likely cause of discomfort for the neonate [79,80].…”
Section: Subcutaneousmentioning
confidence: 99%
“…Additionally, it has been observed that the drug can sometimes leak from the depot formed at the injection site [80]. This issue may be compounded by the relatively smaller proportion of subcutaneous fat in neonates compared with adults [15].…”
Section: Subcutaneousmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 1 study in this meta-analysis reported an increase in ROP among recipients of Epo, a single-center study by Romagnoli et al 14 In revised meta-analyses 15,16 of the 27 studies randomizing 2209 infants to early Epo or placebo, the incidence of ROP was reported in 7 studies, comprising only 36% of all study infants. Despite their initial report in 2000, Romagnoli et al continued to study Epo, 17 and Epo is currently standard of care in their unit. 17 …”
mentioning
confidence: 99%
“…Despite their initial report in 2000, Romagnoli et al continued to study Epo, 17 and Epo is currently standard of care in their unit. 17 …”
mentioning
confidence: 99%